Prevention of anterior cruciate ligament injuries in female basketball players in japan: an intervention study over four seasons. Issue 4 (27th March 2011) - Nagano, Y; Miki, H; Tsuda, K; Shimizu, Y; Fukubayashi, T
Abstract : Background: Female basketball players are at a higher risk of anterior cruciate ligament (ACL) injury than male players. Therefore, prevention of ACL injury in the former group is essential. Objective: To assess the effect of an injury prevention training program on the incidence of ACL injuries in female basketball players. Design: Prospective intervention study. Setting: Top-level league in Japan. Participants: Players from 12 top-league teams. The control season (2006–2007) included 158 players; the first intervention season (2007–2008), 168 players; the second intervention season (2008–2009), 174 players; and the third intervention season (2009–2010), 162 players. Interventions: From the middle of the 2007–2008 season, a 3-step injury prevention program was initiated. The program focused on strength, balance, jump-landing techniques, and basketball skills. Subjects were instructed to perform exercises in a neutral position and to avoid lumbar lordosis, rear axial weight bearing, hip adduction, and knee valgus. Main outcome measurements: Number and rate of ACL injuries during the four seasons and compliance with the program. Injury incidences were given in terms of per 1000 player-hours (PH). Results: Seven non-contact ACL injuries were noted during the control season (0.059/1000 PH); 4, during the first intervention season (0.031/1000 PH); 10, during the second intervention season (0.073/1000 PH); and 2, during the third intervention season (0.016/1000 PH). During the second intervention season, the rate of ACL injuries in the teams that complied with the program was 0.053/1000 PH, while the rate in the teams that did not comply was 0.099/1000 PH. During the third intervention season, the rate of ACL injuries in the teams that complied was 0.011/1000 PH, while the rate in the teams that did not comply was 0.032/1000 PH. Conclusion: The results show that the injury prevention program tended to decrease the frequency of ACL injuries.